O tarapatach tożsamości w ciasnym świecie - Bauman, Zygmunt (Er(r)go. Teoria - Literatura - Kultura, 2003)
Zygmunt Bauman "On the Exigencies of Identity in a Tight World" Zygmunt Bauman's essay begins with an analysis of the political and social situation in selected European countries where leading politicians nurture xenophobia and pander to fears of crime. Bauman describes population and immigration surpluses in terms of "human waste" produced by the introduction and imposition of social order and economic progress. This has led to the emergence of the "social recuperation" industry. At the same time the traditional division of the world into the homely and civilised places which"we" occupy and isolated no-man's-lands as well as uncultivated expanses in need of colonisation has disappeared. The world has become a tighter place to live in. In those globalised circumstances the question of identity is particularly pressing. Bauman argues that the identity fostered by such circumstances cannot be a product of self-definition. Rather, it is forged and imposed by others, beyond the control of its bearer. Thus identity appears to be an agonistic notion which makes us seek and castigate the other/alien in us. The trouble with identity, Bauman concludes, is a global issue; it cannot be solved on a local scale.